Identifying barriers to physical activity participation and engagement among college students in Riyadh (Saudi Arabia): gender differences in perceived barriers - Prieto-González, Pablo; Alkouatli, Claire (Frontiers in Sports and Active Living, 2025)
ObjectiveDespite growing public health efforts worldwide, many young adults—particularly women—remain insufficiently active, often due to a complex interplay of personal, social, and environmental barriers. In the context of rapid sociocultural change in Saudi Arabia, this descriptive study aims to identify and compare perceived barriers to physical activity (PA) among male and female college students in Riyadh across key domains.MethodsThis cross-sectional observational study included 437 college students (219 females and 218 males), aged 18–25 and residing in Riyadh. Data were collected in person using a validated, self-administered questionnaire comprising 39 items across nine domains assessing barriers and behavioral aspects related to PA.ResultsSignificant gender differences emerged in barriers such as harassment, lack of friend support, body image concerns, safety, weather, and the absence of same-gender role models. No differences were observed in PA frequency. Key factors negatively affecting PA frequency included competing priorities, weather, transportation, and fatigue. Engagement in more structured or competitive activities was hindered by environmental pollution, time management challenges, limited group support, lack of skills, and absence of role models. However, effect sizes were generally small, and the predictive power of the models was modest.ConclusionGender disparities in perceived barriers were most pronounced in personal, sociocultural, environmental, and health-related domains, influencing the type of PA more than its frequency. Although some gender differences were statistically significant, their effect sizes are small and should be interpreted with caution. Promoting equitable participation requires safe, female-friendly environments, stronger peer and role model support, and improved access to equipment and green spaces. Addressing body image, personal safety, confidence, skills, and time management is also essential. Given the modest predictive power of the models, other factors likely influence PA behaviors and warrant further investigation.